Energy Price Reform: A Guide for Policymakers - David Coady; Ian Parry; Baoping Shang (Center for Economic Studies and ifo Institute (CESifo), 2017)
This essay reviews the conceptual and quantitative literature on the efficient system of fossil fuel energy prices in different countries for reflecting supply and environmental costs, as well as the environmental, fiscal, and economic benefits from energy price reform. Drawing on recent experiences in numerous countries, the ingredients for successful reform are then discussed (e.g., the need for a comprehensive reform strategy and for compensating vulnerable groups). Low energy prices, fiscal pressures, and momentum for climate action provide an especially conducive environment for price reform and much is happening rapidly on the ground, however there is a long way to go to reap the enormous benefits at stake (e.g., at the global level, over a 20 percent reduction in carbon emissions and revenues gains of 4 percent of GDP).
Keywords: Q31; Q35; Q38; 330; energy price reform; efficient taxation; environmental externalities; reform experiences